2020
DOI: 10.1016/j.jallcom.2020.153977
|View full text |Cite
|
Sign up to set email alerts
|

Unique hybrid precipitate structures forming in an Al–Cu–Mg–Si alloy

Abstract: Crystal structures of hybrid precipitates have been analysed by atomic-resolution scanning transmission electron microscopy in an aged AleCueMgeSi alloy. A new unique hybrid precipitate (UHP) has been found as rod-shaped discrete particles along C100D Al in bulk aluminium matrix. The UHP consists of a core with local 4-fold symmetry surrounded by GPB zone unit pillars often combined with monoatomic Cu layers in fcc-Al matrix. A certain atomic configuration fragment of the UHP structure is often seen to inter-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Foils for transmission electron microscopy (TEM) were prepared using conventional methods [11] and studied in two microscopes operated at 200 kV: a JEOL JEM-2100F and a JEOL ARM-200F, the latter being double aberration corrected. The TEM settings given in Table S1 were used for acquisition of STEM images [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Foils for transmission electron microscopy (TEM) were prepared using conventional methods [11] and studied in two microscopes operated at 200 kV: a JEOL JEM-2100F and a JEOL ARM-200F, the latter being double aberration corrected. The TEM settings given in Table S1 were used for acquisition of STEM images [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Zn is also observed to have a more distinct effect on precipitate crystal structures that, to the best of the authors’ knowledge, have not been described previously; see Figures c, b,d, and a,b. It promotes the formation of defects with extended 2-fold symmetry and mirror plane configurations, which is not observed in precipitates nucleated in pure Al–Mg–Si alloys or with Ag, Li, and Cu additions. ,, ,,,, Moreover, Zn shows less tendency than Cu to occupy the β″/Al matrix interface periodically, but Zn incorporates preferentially on the Si 2 , Si 3 /Al sites of the β″ structures, which also suppresses misfit dislocations; see Figure c,d. It is interesting to note that Zn suppressed misfit dislocations even in the precipitates comprised of β″ and β′′ 2 structures; see Figure a.…”
Section: Discussionmentioning
confidence: 98%
“…However, the distribution of Si and Mg exactly coincides with other needleshaped phases, as shown by the red arrows in Figure 9d,e. They are invisible in the HAADF image due to the very close atomic numbers of Mg (12), Al (13), and Si (14). In the TEM results, these phases are estimated to be β′-Mg2Si precipitates.…”
Section: Tem Observation Of An Al-si-mg-cr-cu Alloymentioning
confidence: 95%
“…As Li et al [12] reported, through a certain heat treatment consisting of solution treatment and artificial aging, the strength of Al-Si cast alloys can be increased considerably. In recent years, it has been reported that adding Cu to Al-Mg-Si alloys can enhance the age-hardening effect of the alloy [13][14][15][16]. Sunde et al [15] found that relatively small changes in the Cu level and the Si:Mg ratio had a significant effect on the resulting distribution of precipitate phases, their structural evolution, and their thermal stability.…”
Section: Introductionmentioning
confidence: 99%